Analisa Perencanaan Persediaan Bahan Produksi dalam UMKM - Feliks Rendra Setiawan; R M Dirgantoro Ario K; Erlinda Novianty; Shelly Priscilia (CV. Syntax Corporation Indonesia, 2021)
UMKM martabak bangka special 21 has been around for about 20 years and of course the owner is already experienced independently in preparing the ingredients needed in martabak processing, but problems start to arise when the owner starts to open a new branch shop, because it is needed a good management system to increase production efficiency. The purpose of this study is to determine the number of requests, the amount of material requirements and determine the method for preparing production materials. Production material requirements planning using lot sizing technique is one step in determining the number of production material orders. The three lot sizing techniques used are least unit cost, least total cost and lot for lot. Of the three techniques, we will find out which technique is the most efficient, by using martabak sales data from february 2019 to january 2020, the results of the february 2020 demand forecast are 2,400 martabak pans. Of the three lot sizing techniques used, the least total cost method is found to be the most efficient method because it produces the least inventory costs for martabak production materials compared to other lot sizing methods.